Evaluation of three doses of Trichoderma harzianum for the control of black scab (Rhizoctonia solani) of potatoes in Huari, Ancash - Alarcón, G. A.; Utia, M. R. (Peruvian Agricultural Research, 2020)
Objectives: To evaluate the effect of three levels of concentration of the biological agent Trichoderma harzianum (Tricho-D) in the control of Rhizoctonia solani potato cv. Yungay in Huari, Ancash. Methods: The research was carried at Tumbos farm, located in the district of Chavin de Huantar, Huari, from November 2018 to February 2019. A completely randomized block design was used, with four treatments (three levels of Tricho-D, and a control). The variables evaluated were: the degree of severity, percentage of incidence, AUDPC, control efficiency, and tuber yield per plant. Results: The dose of 0.3 kg ha-1 of Tricho-D reported less severity with a degree of 0.75 and 7.5% incidence of R. solani disease. Likewise, the dose of 0.3 kg ha-1 of Tricho-D had an effect antagonistic about the fungus R. solani obtaining a high control efficiency with 82.5%. The highest dose of 0.3 kg ha-1 of Tricho-D reported a higher yield per plant with 757.5 g plant-1 in cv. Yungay. Conclusions: The dose of 0.3 kg ha-1 of Tricho-D had an antagonistic effect with the parasitic activity of the R. solani fungus controlling the black scab in potatoes cv. Yungay under field conditions in Chavín of Huantar, Huari-Ancash.